Review and Recommendation of Cold Asphalt Emulsion Mixtures Caems Design - I Nyoman Arya Thanaya (Institute of Research and Community Outreach - Petra Christian University, 2007)
Note from the Editor Cold Asphalt Emulsion Mixture (CAEM) is a mixture of aggregates and asphalt emulsion that is mixed at room temperature. It is relatively simple to produce, but the design procedure provided by the Asphalt Institute and the Ministry of Public Work of Indonesia pose some problems in its practical application. This Technical Note discusses limitations of the current design procedures and presents a simpler and more practicable design procedure